2008
DOI: 10.1002/hlca.200890164
|View full text |Cite
|
Sign up to set email alerts
|

Retention Behavior of Neutral and Positively and Negatively Charged Solutes on an Immobilized‐Artificial‐Membrane (IAM) Stationary Phase

Abstract: The retention behavior of neutral, positively charged, and negatively charged solutes on the IAM.PC.DD2 stationary phase was investigated and compared. A set of monofunctional compounds and complex drugs (steroids, nonsteroidal anti-inflammatory drugs, and b-blockers) were selected for this study, i.e., neutral solutes and solutes with acidic or basic functionalities which are positively charged or negatively charged at pH 7.0. The correlation between the retention factor log k w at pH 7.0 on the IAM.PC.DD2 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
4
12
0
Order By: Relevance
“…3, a, shows that b-blockers which are positively charged at the experimental conditions are retained strongest on the ILC column among the three sets of solutes. The same result was also found for IAM chromatography [21]. This suggests that the interaction of ionized drugs with immobilized liposomes depends not only on their lipophilicity expressed as log P oct , but also on additional interactions including electrostatic interactions and their ability to form H-bonds with the polar head groups of the phospholipids (b-blockers can form more H-bonds than alkyl(4-methylbenzyl)-amines).…”
Section: :0supporting
confidence: 73%
See 3 more Smart Citations
“…3, a, shows that b-blockers which are positively charged at the experimental conditions are retained strongest on the ILC column among the three sets of solutes. The same result was also found for IAM chromatography [21]. This suggests that the interaction of ionized drugs with immobilized liposomes depends not only on their lipophilicity expressed as log P oct , but also on additional interactions including electrostatic interactions and their ability to form H-bonds with the polar head groups of the phospholipids (b-blockers can form more H-bonds than alkyl(4-methylbenzyl)-amines).…”
Section: :0supporting
confidence: 73%
“…It was found that positively charged solutes are more retained than negatively charged solutes on an IAM.PC.DD2 stationary phase [21], which was explained as the result of a larger affinity of positively charged drugs to phospholipid membranes compared to the negatively charged compounds. However, we did not obtain the same results by ILC with immobilized unilamellar egg PC liposomes in this study.…”
Section: :0mentioning
confidence: 92%
See 2 more Smart Citations
“…The interaction of drugs with phospholipids has been investigated by IAM-HPLC for different sets of neutral and charged compounds such as β-blockers (90), non-steroidal anti-inflammatory drugs (NSAIDs) (91), dihydropyridine (DHPs) calcium channel blockers (92), and for a set of compounds with a wide structural diversity (93). It was found that log k IAMw values from IAM columns correlate with log P oct only for neutral and structurally related compounds and that electrostatic interactions between the charged solutes and the polar heads of phospholipid play a vital role in IAMs.…”
Section: Immobilized Artificial Membrane (Iam) Chromatographymentioning
confidence: 99%